Oito votos contra um: o desenvolvimento da ciência eugenista nos Estados Unidos - Cruz, Rodrigo Andrade da (2012)
The present study focused on the development and institutionalization of the science of eugenics in the United States during the first decades of the 20th century. For this purpose, we focused on the ideas of Charles B. Davenport (1866-1944), his work team, and the institutional networks he contributed to establish. Davenport initially learned the notions and methods developed for eugenic research by Francis Galton (1822-1911) and Karl Pearson (1857-1936), who essentially applied statistical methods. However, by the same time the studies by Gregor Mendel (1822-1884) were rediscovered giving impetus to the incipient field of genetics and were also assimilated by Davenport into his eugenic project. Together with a discussion of the overall historical context that favored the development of eugenics in the US, we analyzed the works by Davenport as well as by some of his main collaborators, such as psychologist Henry Goddard (1866-1957) and eugenicist Harry Laughlin (1880-1943), as well as the repercussions of eugenics in US society in the early decades of the 20th century